Multiparty Session Actors - Rumyana Neykova; Nobuko Yoshida (Logical Methods in Computer Science, 2017)
Actor coordination armoured with a suitable protocol description language has been a pressing problem in the actors community. We study the applicability of multiparty session type (MPST) protocols for verification of actor programs. We incorporate sessions to actors by introducing minimum additions to the model such as the notion of actor roles and protocol mailboxes. The framework uses Scribble, which is a protocol description language based on multiparty session types. Our programming model supports actor-like syntax and runtime verification mechanism guaranteeing communication safety of the participating entities. An actor can implement multiple roles in a similar way as an object can implement multiple interfaces. Multiple roles allow for cooperative inter-concurrency in a single actor. We demonstrate our framework by designing and implementing a session actor library in Python and its runtime verification mechanism. Benchmark results demonstrate that the runtime checks induce negligible overhead. We evaluate the applicability of our verification framework to specify actor interactions by implementing twelve examples from an actor benchmark suit.